DISPARITAS PEMIDANAAN DALAM PASAL 81 UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (Studi di Pengadilan Negeri Sukoharjo dan Pengadilan Negeri Boyolali) DISPARITY OF SENTENCING IN ARTICLE 81 ACT NUMBER 23 OF 2002 ON CHILD PROTECTION (Researched In Sukoharjo District Court And Boyolali District Court) - Dwi Kurniawan, Deny; Purnama, Galuh Indra (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractDisparity of sentencing is not the same application on the same criminal act, it can be bad if the defendant or the victim comparing him with the decision handed down the same verdict yet another different decision,it is getting worse if the victim or the defendant is a child, particularly in the crime of child rape.Children should receive special treatment in the law because the child has a psychological condition that is less prepared to face severe criminal sanctions and different from the same decision but a different verdict .In this journal the authors conducted a study using interviews with judges who had handled the child rape cases committed in the District Court and Boyolali Sukoharjo to discover how the disparity can occur in the criminal offense of child rape and efforts to address disparities criminal onset.Keywords: Disparities criminal,Child rape, Punishment of Article 81 of Law No. 23 of 2002.